Effect of three processing methods on the functional properties of mung bean flour - Malaluan, Ma. Roxanne R.
ABSTRACT The effects of three pretreatments, namely, soaking, boiling, and roasting on the physicochemical and functional properties of mung bean flours were determined. The roasted flour was darker and brownish in color compared to the other flours. The flours belonged to low acid (6.45-6.54), low moisture (5.11-9.17%) foods and were assumed to have good storage behaviors. Starch content values were significantly different from each other, with boiled flour as the highest (57.31%). Protein content values (23.29-23.73%), which were twice as much as the protein content of all-purpose flour, had no significant differences. Maximum protein solubility (63.0%) was recorded for soaked mung bean flour, which also had the highest gelation capacity. The heated flours had water absorption capacities (165.5-178.4%) that were significantly higher than the soaked flour (128.2%). The obtained values for oil absorption capacity (128.8-146.4%) were not significantly different from each other. In terms of foam and emulsion capacities, soaked flour was the highest (13.0 g/ml and 6.4 ml/g, respectively). However, these properties were inactivated in the case of roasted flour. The most stable foams and emulsions were produced by the boiled flours (which retained 81.0% and 85.7% of the original foam and emulsion volume, respectively after 2 hrs). Overall, soaking and boiling produced mung bean flours of good functional properties. On the contrary, roasting impaired most of the functional properties and therefore would not be ideal for processing mung bean flours intended for food application.